The Eighth Five Year Plan 1992 -1997 Volume I - Planning Commission (Planning Commission, 1992)
The launching of the First Five Year Plan in April 1951 initiated a process of development aimed not only at raising the standard of living of the people but also opening out to them new opportunities for a richer and more varied life. This was sought to be achieved by planning for growth, modernisation, self-reliance and social justice. We have come a long way over the past forty years. A largely agrarian feudal economy at the time of independence has been transformed into one based on a well developed and a highly diversified infrastructure with immense potential for industrialisation.
Planning Commission New Delhi